Analisis Kemampuan Bersaing Ekspor Komoditi Kopi dan Kakao Indonesia di Pasar Internasional - Muyas, Sinta Mufidah; Kartika Fajar Nieamah (Jurnal Manajemen Dirgantara, 2025)
This study examines the competitiveness of Indonesia's coffee and cocoa export commodities in the international market from 2009 to 2023 and evaluates their trade positions. By utilizing 15 years of secondary data, the Revealed Comparative Advantage (RCA) method assesses competitiveness, while the Trade Specialization Index (ISP) method analyzes trade growth. Findings indicate that Indonesia demonstrates strong competitiveness in coffee (RCA 4.87) and cocoa (RCA 6.16), ranking second globally after Brazil and the Netherlands, while outperforming Switzerland and Canada. The trade position identifies Indonesia as an exporter in the growth stage for both commodities. These results underscore the substantial potential of Indonesia's coffee and cocoa exports within the global market.